Maryland's All-Payer Health Care System: A Light at the End of a Tunnel. Issue 1 (January 2018) - Bakhamis, Lama; Matsumoto, Taeko; Tran, Mary; Paul, David P.; Coustasse, Alberto
Abstract : The state of Maryland, in collaboration with the Centers for Medicare & Medicaid Services, developed the first all-payer system model in the Unites States in 1971 and 35 years later in response to financial pressures undertook to modernize this program. The focus of the modernized program was to improve overall per-capita expenditure, quality of care, and the outcome of Marylanders' health. The financial status of Maryland hospitals was declining because of the rate setting of the Health Services Cost Review Commission while hospital admission rates and spending were increasing. This study showed positive change in moving Maryland health care delivery model in hospitals from volume-driven care to value-driven coordinated care. Maryland hospitals have changed their mind-sets to achieve the Triple Aim of cost reduction, health improvement, and quality-of-care improvement. The modernized model does require hospitals and business individuals to change their approach to be accountable in providing health care to all citizens, as well as trying to solve chronic social problems such as poverty and unequal access to health care.